An Acculturation in The Composition and Creative Process of Dengklung Music in Bandar Village, Batang Regency - Wulandari, Eky Olivia; Utomo, Udi; Florentinus, Totok Sumaryanto (Universitas Negeri Semarang, 2020)
Dengklung Al Kafi art is one of the traditional performing arts which is a combination of two cultures, namely Javanese and Arabic or Islamic from Bandar village, Batang regency. The purpose of this study was to analyze and describe the acculturation and creative process of the Dengklung Al Kafi art in Bandar village, Batang Regency. The method used was qualitative with ethnomusicology and anthropology approaches. The data collection techniques used were observation, interviews, and document study. The data validity technique used was the source triangulation technique. The analysis process started from the data collection, data reduction and clarification, drawing conclusions and interpretation. The results showed that cultural acculturation was found in aspects of Dengklung art performances namely musical instruments, lyrics, dance and costume. In addition, creativity in Dengklung art can be seen by the creative process of notation change from pentatonic to diatonic, then added with aspects of dance and costume that combine Javanese and Arabic elements. The combination of culture which is manifested in the form of Dengklung art has been accepted and even appreciated by the surrounding community, it caused this art to stands until now.